2020
DOI: 10.1101/2020.02.21.959635
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ketogenic Diet Prevents Heart Failure from Defective Mitochondrial Pyruvate Metabolism

Abstract: The myocardium is metabolically flexible and can use fatty acids, glucose, lactate/pyruvate, ketones, or amino acids to fuel mechanical work. However, impaired metabolic flexibility is associated with cardiac dysfunction in conditions including diabetes and heart failure. The mitochondrial pyruvate carrier (MPC) is required for pyruvate metabolism and is composed of a hetero-oligomer of two proteins known as MPC1 and MPC2. Interestingly, MPC1 and MPC2 expression is downregulated in failing human hearts and in … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 80 publications
0
7
0
Order By: Relevance
“…Because both rapamycin and trichostatin A improve mitochondrial oxidative metabolism in normal hearts ( 48 , 49 , 50 , 51 , 52 , 53 ), our data suggested that restoration of cardiac fatty acid oxidation is required for the effectiveness of these therapies. In agreement, both high-fat diet and medium-chain ketogenic diet were shown to improve severe cardiac hypertrophy in models of impaired cardiac pyruvate oxidation ( 21 , 34 ). These results suggest that increased flux of either ketones or fatty acids through oxidative metabolism can compensate for the loss of carbohydrate-oxidative metabolism and restore cardiac structure.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…Because both rapamycin and trichostatin A improve mitochondrial oxidative metabolism in normal hearts ( 48 , 49 , 50 , 51 , 52 , 53 ), our data suggested that restoration of cardiac fatty acid oxidation is required for the effectiveness of these therapies. In agreement, both high-fat diet and medium-chain ketogenic diet were shown to improve severe cardiac hypertrophy in models of impaired cardiac pyruvate oxidation ( 21 , 34 ). These results suggest that increased flux of either ketones or fatty acids through oxidative metabolism can compensate for the loss of carbohydrate-oxidative metabolism and restore cardiac structure.…”
Section: Discussionmentioning
confidence: 58%
“…Octanoate boluses and medium-chain ketogenic diets can increase circulating ketone bodies ( 33 ) because of stimulation of high rates of medium-chain mFAO flux in the liver. Importantly, medium-chain ketogenic diets can completely revert severe cardiac hypertrophy in models of impaired cardiac pyruvate oxidation ( 21 , 34 ). Thus, to test the ability of highly enriched medium-chain ketotic feeding to alleviate the cardiac phenotype in the absence of carnitine mediated-fatty acid oxidation, a diet was formulated with octanoate (OctD) as a majority of the diet.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Trehalose and LT reduced fructose‐induced hepatic steatosis and induced hepatocyte fasting response signals, PGC1α, TFEB, and FGF21. Extrahepatic cardiometabolic effects of these compounds are broad, including peripheral insulin sensitization [118], activating peripheral thermogenesis, reduced adipocyte hypertrophy [119,120], in addition to reduced atherosclerotic plaque lesion area [27,121] and pathological cardiac remodeling in response to injury [122,123], that mimicked ketogenic dietary effects on heart failure [37]. Treating liver‐specific GLUT8‐deficient mice with oral trehalose did not increase the efficacy of trehalose on diet‐induced hepatic steatosis, which implies some mechanistic overlap between GLUT8 deletion and trehalose action [9].…”
Section: Restricting Hepatocyte Carbohydrate Entry Mimics the Broader...mentioning
confidence: 99%
“…Moreover, in children with NAFLD, low‐glycemic index foods reduced systolic blood pressure, plasma ALT, and insulin resistance indices (HOMA‐IR) after 3‐ and 6‐month treatment [35]. In mice, ketogenic diets reduce circulating lipids, intrahepatic lipids, and insulin resistance markers [36], and improve cardiac function during heart failure [37]. In balance of these findings, low‐carbohydrate diets in some contexts do not outperform other forms of caloric restriction [38].…”
Section: Clinical Utility Of Cr If and Reduced Dietary Carbohydratementioning
confidence: 99%